Приключения Ульяны Караваевой - Варденбург Дарья (Лучшие книги детства, 2016)
Экземпляры: ф.6 (20160415) / Инвентарный номер: 51552 / Цена: 50.00 / Авт.знак: В 18 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6